A guide to starting your hedge fund - Serrano Berntsen, Erik, 1983- (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2015)
"Successful hedge fund investing begins with well-informedstrategyA Guide to Starting Your Hedge Fund is a practical, definitive "how-to" guide, designed to help managers design andlaunch their own funds, and to help investors select and diligencenew funds. The first book to examine the practical aspects ofsetting up and operating funds with a focus on energy commoditymarkets, this book scrutinises the due diligence process andcomprehensively reviews the opportunities and risks of all energycommodity markets as hedge fund investments. Extensive planning andstrategy advice prove invaluable to prospective fund managers andinvestors alike, and detailed discussion of the markets'constraints help inform procedural decisions. Readers gain insightinto practical matters including legal and commercial structures, due diligence, fund raising, operations, and more, allowing them toconstruct a concrete investment plan before ever touching apenny. Asset managers are looking to energy commodities to provideattractive uncorrelated - if volatile - returns. Thesehigh returns, however, are accompanied by high risk. Few investorshave experience evaluating these investment opportunities, and fewprospective fund managers understand the market fundamentals andtheir associated risks. This book provides the answers sorelylacking in hedge fund literature, giving investors and fundmanagers the background they need to make smarter decisions. Understand the markets' structures, opportunities, andrisks Develop a comprehensive, well-informed investment strategy Conduct thorough due diligence with a detailed plan Examine the practical aspects of fund raising, legal and taxstructure, and more Oil has long been traded by hedge funds, but electricity, thefuels that generate electricity, and the environmental productslike emissions allowances and weather derivatives have become thenew "hot" investment strategies. These high returns come withhigher risk, but A Guide to Starting Your Hedge Fund ensuresparticipants have essential information at their disposal"--
Asset Allocation: Understanding Different StrategiesChecklist for Investing in Energy Commodity Hedge Funds; Bibliography; Chapter 11 Quo Vadis; Bibliography; Appendix A Sample Business Plan Outline; Appendix B Outline of a Confidential Explanatory Memorandum: Sample Offshore Feeder Ltd; Appendix C Sample Due Diligence Questionnaire Outline; Index; EULA.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Hedge funds; Business; Hedge funds; Investments -- Management; BUSINESS & ECONOMICS -- Finance; Hedge funds; Electronic books; Electronic books